Answer
a) As t increases, x increases and y decreases.
b)
$y=1-x^{2}$
$x \geq 0$
![](https://gradesaver.s3.amazonaws.com/uploads/solution/d9c3e2ad-80e7-4b76-9192-df8f2bb91aa0/result_image/1513148522.png?X-Amz-Algorithm=AWS4-HMAC-SHA256&X-Amz-Credential=AKIAJVAXHCSURVZEX5QQ%2F20250215%2Fus-east-1%2Fs3%2Faws4_request&X-Amz-Date=20250215T143504Z&X-Amz-Expires=900&X-Amz-SignedHeaders=host&X-Amz-Signature=76c4b6bbd05375630b4f310791afcd6d5add49fcd8b0227529a411d37715073f)
Work Step by Step
a)
$x=\sqrt t$
$y=1-t$
When,
t=-2 x=undefined y=3
t=-1 x=undefined y=2
t=0 x=0 y=1
t=1 x= 1 y=0
t=2 $x=\sqrt 2$ y=-1
t=3 $x=\sqrt 3$ y=-2
b)
$x=\sqrt t$
$x^{2}=t$
$y=1-t$
$y=1-x^{2}$
From part a), we can infer that $x \geq 0$ because x is undefined at any negative t values.